2018
DOI: 10.1161/jaha.118.009384
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD74 Reroutes MIF/CXCR4/AKT‐Mediated Survival of Cardiac Myofibroblasts to Necroptosis

Abstract: BackgroundAlthough macrophage migration inhibitory factor (MIF) has been demonstrated to mediate cardioprotection in ischemia/reperfusion injury and antagonize fibrotic effects through its receptor, CD74, the function of the soluble CD74 receptor ectodomain (sCD74) and its interaction with circulating MIF have not been explored in cardiac disease.Methods and ResultsCardiac fibroblasts were isolated from hearts of neonatal mice and differentiated into myofibroblasts. Co‐treatment with recombinant MIF and sCD74 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 76 publications
2
39
0
Order By: Relevance
“…Heart rate variability is further reduced in patients developing ACLF and can be used to predict disease progression and short-term mortality (45). Interestingly, mincle is also expressed in cardiac tissue (46). We also observed an upregulation of mincle in cardiac tissue in the model of ACLF.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Heart rate variability is further reduced in patients developing ACLF and can be used to predict disease progression and short-term mortality (45). Interestingly, mincle is also expressed in cardiac tissue (46). We also observed an upregulation of mincle in cardiac tissue in the model of ACLF.…”
Section: Discussionmentioning
confidence: 51%
“…We also observed an upregulation of mincle in cardiac tissue in the model of ACLF. This may be explained by cell dysfunction, whereby mincle induces necroptosis (46).…”
Section: Discussionmentioning
confidence: 99%
“…As the yeast CXCR4-transformant experiments also implied a role in the activation of signal transduction, we focused on CXCR4 for subsequent functional studies and next asked whether AtMDLs would also trigger MIF-like CXCR4-facilitated signaling responses in mammalian cells. The MIF-/CXCR4-induced PI3K/Akt signaling cascade is a well-studied MIF-mediated response pathway with physiological-/pathophysiological relevance in human macrophages and T cells, as well as for cancer cell survival (20,48,49). We performed signaling studies in HEK293 cells stably overexpressing CXCR4 (HEK293-CXCR4), fostering appreciable surface expression levels of CXCR4 (Supplementary Figure 4B).…”
Section: Atmdls Bind To and Signal Through Human Mif Receptorsmentioning
confidence: 99%
“…The MIF/CXCR4 signaling axis controls monocyte, T-cell, and B-cell infiltration in atherosclerosis and other inflammatory conditions (17,19). It also contributes to cancer metastasis, cardiac fibroblast survival, and eosinophil inflammation (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…TLR4 has been reported to be related to new-onset atrial fibrillation in acute myocardial infarction [25]. Soppert's study has shown that CXCR4 is involved in myofibroblast necroptosis, which may modulate cardiac remodeling in heart failure [26]. Based on these studies, we speculate that these 3 genes may be a novel target for atrial fibrillation treatment.…”
Section: Discussionmentioning
confidence: 68%